2015
DOI: 10.1016/j.cmet.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Myc Induces Expression of Glutamine Synthetase through Promoter Demethylation

Abstract: Summary c-Myc is known to promotes glutamine usage by up-regulating glutaminase (GLS), which converts glutamine to glutamate that is catabolized in the TCA cycle. Here we report that in a number of human and murine cells and cancers, Myc induces elevated expression of glutamate-ammonia ligase (GLUL), also termed glutamine synthetase (GS), which catalyzes the de novo synthesis of glutamine from glutamate and ammonia. This is through upregulation of a Myc transcriptional target thymine DNA glycosylase (TDG), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
190
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(209 citation statements)
references
References 33 publications
19
190
0
Order By: Relevance
“…Some tumors, however, also upregulate GS and glutamine synthesis (He et al, 2010; van der Vos et al, 2012). In a number of breast cancer and glioblastoma cell lines, increased GS activity and de novo synthesis of glutamine is essential for cell survival, growth, and proliferation under limited supply of exogenous glutamine (Bott et al, 2015; Tardito et al, 2015). In such cases, newly synthesized glutamine mainly contributes to the biosynthesis of nucleotides and asparagine, and to the transport of essential amino acids.…”
Section: Mitochondria Integrate Catabolism Anabolism and Signalingmentioning
confidence: 99%
“…Some tumors, however, also upregulate GS and glutamine synthesis (He et al, 2010; van der Vos et al, 2012). In a number of breast cancer and glioblastoma cell lines, increased GS activity and de novo synthesis of glutamine is essential for cell survival, growth, and proliferation under limited supply of exogenous glutamine (Bott et al, 2015; Tardito et al, 2015). In such cases, newly synthesized glutamine mainly contributes to the biosynthesis of nucleotides and asparagine, and to the transport of essential amino acids.…”
Section: Mitochondria Integrate Catabolism Anabolism and Signalingmentioning
confidence: 99%
“…The expression of pyruvate carboxylase, which can provide carbon to the TCA cycle through its conversion of pyruvate to oxaloacetate, represents a potential mechanism for glutaminase independence 120,175 . Glutamine synthetase (GLUL) expression may also predict glutamine independence and promote BPTES resistance 171,[176][177][178] .…”
Section: Therapymentioning
confidence: 99%
“…As a result, some tumor cells require large amounts of exogenous glutamine to generate building blocks and energy for their growth and survival. In contrast, various tumor cell lines with high expression levels of GS enzyme can synthesize glutamine de novo and can grow and proliferate in the absence of exogenous glutamine (12)(13)(14).Befitting its critical role in nitrogen metabolism, GS activity is tightly regulated. Pioneering studies by Stadtman's group (15) and others demonstrated that bacterial GS is subject to complex feedback regulation by glutamine and downstream metabolites by reversible adenylylation and deadenylylation of a specific tyrosine residue, resulting in the inactivation of .…”
mentioning
confidence: 99%
“…As a result, some tumor cells require large amounts of exogenous glutamine to generate building blocks and energy for their growth and survival. In contrast, various tumor cell lines with high expression levels of GS enzyme can synthesize glutamine de novo and can grow and proliferate in the absence of exogenous glutamine (12)(13)(14).…”
mentioning
confidence: 99%